PENDAPATAN MASYARAKAT DALAM PEMANFAATAN HASIL HUTAN TEMBAWANG DI DUSUN PERONGKAN KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Tari, Marisstella; Muin, Sudirman; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2017)
Tembawang forest is a land use system by local communities in West Kalimantan and has important role for viability of society, both in terms of economic, social, cultural and ecological. People who live around the forest tembawang mostly worked as a farmer with herd of tembawang forest products. The aim this research to knew about actual amount Perongkan village society revenue which sourced from tembawang forest products utilization, the degree of difference between Perongkan village society revenue sourced tembawang forest products with the revenue which comes from not tembawang product and the factors which affect to Perongkan village society revenue sourced tembawang forest products. The method which used in this research were surveyed method descriptive research and associative. Sampling was done by purposive random sampling method with respondents number of 52 households. Data analyzed using descriptive analysis, paired samples T-test analysis and Spearman's rho correlation.These results indicate that income which obtained by society from tembawang forest products an average of Rp 1,958,063 / household / month, based on two different test paired samples showed a significant difference between the average revenue from tembawang forest products of 60, 79% with an average revenue which sourced from outside tembawang of 39.21% and the factors that affect people's revenue by Spearman's rho test showed the labor factor significantly influence people's revenue in the utilization of tembawang forest products, whereas land area factor and utilized type was not significant influence to people's revenue in the utilization of tembawang forest products. Keywords: Income Community, Perongkan Village, Tembawang Forest